Welfare Effects of Changes in Income Tax Progression in Sweden - Ulf Jakobsson; Göran Normann (The Research Institute of Industrial Economics (IUI), 1976)
Within the framework given by the theory of optimal income taxation this paper investigates the progressivity of the Swedish income tax. On the assumption that taxes distort labour leisure choice some tax reforms are designed that improve social welfare while keeping tax revenues unchanged. The instrument used in the analysis is an extended version of a model for simulation of the Swedish system of personal income taxation earlier developed by the authors.
Keywords: E62; H21; 330; Income tax; welfare effetcs